Countermeasure SDN-based IoT threats using blockchain multicontroller. (3rd April 2023) - Janani, K.; Ramamoorthy, S.
The Internet of Things (IoT) is making significant progress in various fields; software-defined networks with multiple controllers have become popular because they make it easier to manage large networks. But they are open to several attacks, which makes controller topologies inconsistent. To solve this problem, we suggest a multi-controller blockchain for software-defined networking (SDN) network. This security architecture combines blockchain and multi-controller SDN and divides the network into several domains. We put forth a blockchain-based solution. This paper proposed a model blockchain-enabled SDN multi-controller architecture for IoT networks that uses a clustering algorithm and a new routing protocol that is both secure and energy-efficient. Experimental results indicate that the cluster-based routing protocol has a greater capacity, a shorter response time, and a lower overall power requirement than other protocols. It has been shown that our proposed architecture outperforms the classic blockchain.